Governmental Kindergartens in Misurata Municipality (A geographical study of the reality of these institutions) (Libya Journal of Geographical Studies, 2024)
In this research, a set of important aspects of kindergartens in Misurata municipality are highlighted, starting with a historical overview of establishing this type of educational institutions, then, proceeding to clarify the form of its spatial distribution in the municipality and the pattern that this distribution takes, as well as, analyzing the reality of  kindergartens conditions, and the extent to which they conform to standards in some developed countries, and finally identifying the difficulties that face this type of institutions in the study area, and also the attempts made by the managers of kindergartens, with the help of public and private institutions, to overcome some of these difficulties. A questionnaire was used to collect data related to this type of institution, while tabular  and cartographic presentation using ArcMap, and also photographs were used as specific tools to display data.The research ended up with some conclusions, the most important of which is that the spatial distribution of governmental kindergartens in Misurata municipality is an unequal distribution, where when applying average nearest neighbor index to kindergarten institutions, it is clear that the spatial distribution of those kindergartens is ( clustered), and most of the governmental kindergarten's buildings not subject to standard specifications and conform to international specifications. The State's failure to provide suitable building to kindergartens forced local officials to modify some buildings and use them as buildings of these institutions. Also, many of them suffer from shortage of supplies and some jobs  according to the job placement schedule for kindergartens.
Keywords: Kindergarten; Kindergarten child; Nanny; Teaching aids; Educational corners